Factors affecting in-service teacher engineering design instruction as a portal for developing science conceptual understanding - Aljohani, Mohammed Abdullah (Kansas State University, 2019)
This mixed-methods study investigated the factors that influence in-service teacher integration of science content and student science conceptual understanding during engineering design instruction. Open-ended questions, classroom observations, and documents analysis were conducted to qualitatively explore the factors impacting science content integration and science conceptual understanding. A cross-sectional survey was conducted to investigate the effect of elementary teacher preparation, self-efficacy for, and beliefs about teaching engineering design on the integration of science content and science conceptual understanding. The research study included a sample of 222 participants who were elementary in-service teachers in the State of Kansas. The significant findings of a Multivariate Analysis of Variance (MANOVA) revealed two factors, which positively influence science content integration and students’ conceptual understanding during engineering design instruction: (a) professional development workshops in teaching engineering design, and (b) experience teaching engineering design. Also, this statistical test indicates undergraduate and graduate academic preparation did not influence science content integration and students’ science conceptual understanding during engineering design instruction. A correlational analysis of the data found that teachers’ self-efficacy of teaching engineering design is statistically correlated to science content integration and students’ science conceptual understanding, while teachers’ beliefs about teaching engineering design is not correlated. A triangulation of the qualitative data analysis presented the dynamic dimension of school priority as a mitigating factor in framing engineering design instruction in K-6 classrooms. The findings of the study illuminate the remarkable variation in elementary teacher professional development to deliver engineering design instruction across Kansas districts, which impacts student progression in sophistication in science reasoning of disciplinary core ideas within an engineering design instructional context. This dimension explains the diminished inclusion of science content during engineering design instruction. The availability and degree of Next Generation Science Standards (NGSS) aligned curricula, professional development, allocated time to teach engineering design compromise the potential for engineering design instruction to develop science conceptual understanding. Elementary teachers reported the need to experience engineering design the elementary science methods course. Future research into the role of the elementary science methods course should be explored as a viable portal for preparing teachers to integrate science content during engineering design instruction as mandated in the NGSS for K-6 classrooms.
Keywords: NGSS; Engineering design instruction; Science conceptual understanding; Science content integration; Mixed methods design